THEORETICAL BASIS FOR DETERMINING THE LEVEL OF GUARANTEES OF AUTOMATED SYSTEMS FROM UNAUTHORIZED ACCESS - Бучик, С. С.; Юдін, О. К.; Нетребко, Р. В. (Science-based technologies, 2017)
The article suggests, shows and analyzes the theoretical basis for determining the level of guarantees of automated systems from unauthorized access. The necessary normative documents of technical protection of information that regulate the procedure for assessing and determining the level of guarantees of automated systems from unauthorized access in Ukraine are reflected. The algorithm of the expert's actions is considered. On the basis of these documents, formalization of the basis for determining the level of guarantees of automated systems against unauthorized access was carried out for the first time. The authors proposed theoretical foundations that make it possible to further improve the expert system that will automatically determine the functional profile of security and the level of guarantees of the automated system from unauthorized access. This will facilitate the work of experts regarding the definition of the security profile, the level of guarantees and the creation of the necessary set of protective equipment, as well as reduce the spent resource of time and material resources.